this post was submitted on 16 Jan 2025
162 points (93.5% liked)

NonCredibleDefense

3687 readers
277 users here now

Rules:

  1. Posts must abide by lemmy.world terms and conditions
  2. No spam or soliciting for money.
  3. No racism or other bigotry allowed.
  4. Obviously nothing illegal.

If you see these please report them.

Related communities:

founded 2 years ago
MODERATORS
 
all 18 comments
sorted by: hot top controversial new old

Oh... Oh dear...

[–] JackGreenEarth@lemm.ee 15 points 2 weeks ago* (last edited 2 weeks ago) (6 children)

That's... not true

2^2 = 4
3^2 = 9

(2^2 +3^2) = 13
(2 + 3)^2 = 5^2 = 25
13 != 25

[–] DahGangalang@infosec.pub 44 points 2 weeks ago (1 children)
[–] ArbitraryValue@sh.itjust.works 37 points 2 weeks ago (1 children)
[–] DahGangalang@infosec.pub 4 points 2 weeks ago (1 children)

Yeah, I guess I just don't like looking at his wildly cocked eyes.

[–] ArbitraryValue@sh.itjust.works 11 points 2 weeks ago* (last edited 2 weeks ago)

It's ironic that I couldn't find a high-res version of this one.

[–] Bgugi@lemmy.world 13 points 2 weeks ago

I'm pretty sure that's part of the joke.

[–] raoul 5 points 2 weeks ago

It's missing 2*abe

[–] affiliate@lemmy.world 4 points 2 weeks ago

it’s true in ℤ/2ℤ

[–] rImITywR@lemmy.world 3 points 2 weeks ago* (last edited 2 weeks ago)
(a+b)^2=a^2 + b^2 + 2ab

By the cancellation law

a^2 + b^2 + 2ab = a^2 + b^2

only when

2ab = 0

So either a=0 or b=0

[–] lseif@sopuli.xyz 2 points 2 weeks ago

erm 13! ≠ 25

[–] yetAnotherUser@discuss.tchncs.de 8 points 2 weeks ago* (last edited 2 weeks ago)

Just use the damn Pascal's triangle!

    1                  = 1 * 1   = (a+b)^0
   1 1                 = 1a + 1b = (a+b)^1
  1 2 1                = 1a^2 + 2ab + 1b^2 = (a+b)^2
 1 3 3 1               = 1a^3 + 3(a^2)b + 3a(b^2) + 1b^3 = (a+b)^3

By the way, I have submitted maths homework that had me continue it up to layer 25. The exercise didn't explicitly state we should use the binomial formula, so why work smart when you can work hard?

(To be fair I just used WolframAlpha to get the values. Had to write down all terms still and do some calculations.)

[–] driving_crooner@lemmy.eco.br 8 points 2 weeks ago

True when a and b are orthogonal.

[–] Maggoty@lemmy.world 3 points 2 weeks ago

All I know is Left Add Right Subtract.

But I do have a pretty rad cannon.

[–] And009@lemmynsfw.com 3 points 2 weeks ago

Self explanatory

[–] mariusafa 2 points 2 weeks ago (1 children)
[–] Chrobin@discuss.tchncs.de 3 points 2 weeks ago

(a+ib)(a-ib) = a^2 + b^2